Current progress in production of flavonoids using systems and synthetic biology platforms - Ku Nurul Aqmar Ku Bahaudin,; Suriana Sabri,; Ahmad Bazli Ramzi,; Leow Thean Chor, Adam Thean Chor; Tewin Tencomnao,; Syarul Nataqain Baharum, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Flavonoid is an industrially-important compound due to its high pharmaceutical and cosmeceutical values. However, conventional methods in extracting and synthesizing flavonoids are costly, laborious and not sustainable due to small amount of natural flavonoids, large amounts of chemicals and space used. Biotechnological production of flavonoids represents a viable and sustainable route especially through the use of metabolic engineering strategies in microbial production hosts. In this review, we will highlight recent strategies for the improving the production of flavonoids using synthetic biology approaches in particular the innovative strategies of genetically-encoded biosensors for in vivo metabolite analysis and high-throughput screening methods using fluorescence-activated cell sorting (FACS). Implementation of transcription factor based-biosensor for microbial flavonoid production and integration of systems and synthetic biology approaches for natural product development will also be discussed.